Advanced composites overview - Mar, James W.; Lagace, Paul A. (New York : Massachusetts Institute of Technology, 1988)
This program discusses characteristics, gain in structure efficiences, matrix materials, product forms, nomenciature, production applications, competition with metals, anisotropocity and technical issues
lecturer : James W. Mar and Paul A. Lagace
Keywords: Composite materials; Composite construction